Lead (Pb) Heavy Metal Content in Lamp shell (Lingula unguis) at Lekok Traditional Market, Pasuruan-East Java - Akhmad Nauval; Husain Latuconsina; Majida Ramadhan (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Heavy metal pollution in marine waters can enter the food chain and negatively impact aquatic organisms' lives. One organism that is susceptible to exposure is the lamp shell (Lingula unguis), which has the ability to bioaccumulate heavy metals and is often consumed by the public. Considering the health risks posed by heavy metals such as lead (Pb), it is important to test the heavy metal content in clams sold in traditional markets. This study aims to determine the presence and levels of heavy metal Pb in the bodies of lamp shell sold at the Lekok Traditional Market, Pasuruan, East Java. Clam samples were taken purposively based on three sizes: small size ± 5 cm, medium size ± 7 cm and large size ± 9 cm. Pb content testing in lamp shell samples used Atomic Absorption Spectroscopy (AAS) after the digestion process. The results showed that Pb metal content ranged from 5.11 - 9.26 ppm in large clams ranging from ± 9 cm, while no Lead (Pb) content was found in small and medium sized lantern clams. Compared with the maximum quality limit for lead (Pb) contamination for food safety for shellfish according to several national standards, samples of large lamp shell (Lingua unguis) sold at the Lekok traditional market in Pasuruan have exceeded the safe threshold for consumption. Therefore, it is advisable to avoid consuming large lantern clams.